Anticoagulant Utilization and Cost Analysis among Cardiology Inpatients in a Tertiary Care Teaching Hospital of Western Nepal - Sabina Sankhi; Nirmal Raj Marasine; Parbati Thapa; Nim Bahadur Dangi (Advances in Pharmacological and Pharmaceutical Sciences)
Introduction. Anticoagulants have a wide spectrum of use and risks associated with their therapy due to their narrow therapeutic range. This study aimed to evaluate the anticoagulant utilization and cost analysis in patients admitted to the cardiology ward of a tertiary care hospital in western Nepal. Methods. A prospective cohort study was conducted in patients admitted to the cardiology ward of Manipal Teaching Hospital (MTH), Pokhara, Kaski, Nepal, from August to November 2019. All patients (n = 132) aged ≥18 years of either gender receiving anticoagulants for any indication in the cardiology ward were included in the study. Anticoagulant utilization, the average prescribed daily dose (PDD/DDD) and the cost of anticoagulant per patient were calculated. Descriptive statistics were performed using IBM-SPSS 20.0. Results. Acute coronary syndrome (66.67%) was a common indication, unfractionated heparin + enoxaparin (45.45%) and enoxaparin (27.3%) were the most frequently prescribed anticoagulants. The performance of monitoring parameters such as international normalized ratio (INR), prothrombin time (PT), activated partial thromboplastin time (aPTT), and renal function test were consistent with the American College of Chest Physician (ACCP) guidelines. The average prescribed daily dose of anticoagulants was 1.3 (unfractionated heparin), 2.25 (enoxaparin), 0.5 (warfarin), and 1.0 (dabigatran). Heparin was associated with the majority of cases of drug interactions (52 cases). Enoxaparin was the most expensive of all the anticoagulant drug classes. The median (IQR) cost of anticoagulants used per patient was US$79.92 ($46.32). Conclusion. Our study suggests that the utilization of unfractionated heparin and enoxaparin and the cost of anticoagulants per patient were higher in the patients admitted to the cardiology ward of the hospital.